Supervision of Municipal Waste Management Fees - Suska, Magdalena (Journal of Finance and Financial Law, 2016)
From Constitutional Tribunal point of view, lawmaker is obliged to create law in possibly clear way. It was not taken into consideration in case of amendment to act from September 13th 1996 regarding keeping cleanliness and order in boroughs. Boroughs had to organize pick up system for municipal waste from property owners, who would have to cover the costs of the whole process as municipal waste management fees. However, the act does not define the character of this fee. As a result there is the uncertainty, which organ of supervising the local self-government units activities is correct to research on resolutions taken basing on keeping cleanliness and order in boroughs act. There are few statements issued by administrative courts, though they are incompatible, despite the fact that were based on same deeds. The article shows the polemic of public bodies.